(untitled) (Research, Society and Development, 2021)
The reuse of endodontic files is a common practice among professionals, although its single use is recommended by the manufacturer. This study aimed to compare the files surface of two heat treated rotating systems manufactured in NiTi: Files # 25/01 and # 25/06 of the ProDesign Logic system and files X1 and X2 of the ProTaper Next system, after 4 steps: unused, first, second and third use, through analysis under scanning electron microscopy. A total of 60 lower incisors were used with only one canal and 20 sets of files, divided into 4 groups (n = 10), according to the different times of use. The files of the control group were submitted to sterilization and placed in the Scanning Electron Microscopy device and the images of the surfaces were obtained and served as a control image. Subsequently, the files were subjected to the first instrumentation in the extracted teeth, washed in an ultrasonic vat with enzymatic detergent and again analyzed in SEM. These procedures were repeated until the third use. Qualitative statistics were used for the presence or absence of surface alteration and application of the chi-square test of partition (p <0.05). The results showed that there was no significant difference between the presence of changes in the experimental times, and after the first use, all files (25.01, 25.06, X1 and X2) showed changes on the surface. It is concluded that the endodontic instruments used in the present research underwent significant superficial changes after the first use, contraindicating their reuse.